2002
DOI: 10.1074/jbc.m203051200
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Norcoclaurine Synthase

Abstract: Norcoclaurine synthase (NCS; EC 4.2.1.78) catalyzes the condensation of dopamine and 4-hydroxyphenylacetaldehyde (4-HPAA) as the first committed step in benzylisoquinoline alkaloid biosynthesis in plants. NCS was purified 1590-fold to homogeneity from cell suspension cultures of meadow rue (Thalictrum flavum ssp. glaucum). The purification procedure, which resulted in a 4.2% yield, involved hydrophobic interaction, anion exchange, hydroxyapatite, and gel filtration chromatography. Purified NCS displayed native… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
64
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(72 citation statements)
references
References 23 publications
1
64
0
4
Order By: Relevance
“…6) and the role of Tyr 108 on the electronic configuration of the dopamine substrate, still need to be fully clarified. Moreover, further studies will be necessary to understand the observed cooperativity in enzyme kinetics (7)(8)(9). At present, only minor ligand-linked tertiary structural changes have been detected at the active site (different rotameric arrangement of Phe 122 in subunit A versus subunit B), whereas the quaternary structures of the substratefree and substrate-bound proteins appear to be essentially superimposable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6) and the role of Tyr 108 on the electronic configuration of the dopamine substrate, still need to be fully clarified. Moreover, further studies will be necessary to understand the observed cooperativity in enzyme kinetics (7)(8)(9). At present, only minor ligand-linked tertiary structural changes have been detected at the active site (different rotameric arrangement of Phe 122 in subunit A versus subunit B), whereas the quaternary structures of the substratefree and substrate-bound proteins appear to be essentially superimposable.…”
Section: Discussionmentioning
confidence: 99%
“…So far, it is also unclear whether the enzyme is assembled in a quaternary structure that could explain the reported cooperativity. In fact, the association state in solution has been reported to be dimeric in gel filtration measurements, whereas NMR investigations indicated that the protein is mostly monomeric (7,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…tenuis cells also did not accept phenylpyruvate as a substrate as did Coptis enzyme. 5 Whereas the formation of norcoclaurine by the condensation of dopamine and 4-HPAA is now clearly established as the central pathway in isoquinoline alkaloid biosynthesis (4,24), the formation of norcoclaurine via the condensation of dopamine and 4-HPAA or via the condensation of dopamine and 4-hydroxyphenylpyruvate was also intensively investigated. The formation of norlaudanosoline through norlaudanosoline 1-carboxylic acid by the condensation of dopamine and 3,4-dihydroxyphenylpyruvate was once seriously considered to be a possible pathway using in vitro and in vivo tracer experiments (23,31).…”
Section: Discussionmentioning
confidence: 99%
“…Only recently has NCS been isolated and characterized from cell suspension cultures of meadow rue (Thalictrum flavum ssp. glaucum) (5,6), but the mechanism of the NCS reaction, including the stereospecificity of product, has not yet been determined.…”
mentioning
confidence: 99%